2008
DOI: 10.2166/wqrj.2008.013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Characterization of Contaminated Soils in Riverbanks of Saint-François and Massawippi Rivers (Southern Québec)

Abstract: Des sols contaminés aux hydrocarbures (C10-C50) et d'autres contaminants ont été découverts récemment dans les berges des rivières Saint-François et Massawippi, entre les municipalités de Eustis et Drummondville (sud du Québec). Il est probable que cette contamination provienne d'un déversement accidentel ou illégal dont la source serait l'ancienne mine de Eustis située au abord de la rivière Massawippi. La couche contaminée se retrouve parfois à plus d'un mètre de profondeur des berges. Malgré qu'il existe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The gap is also very small (±0.006) for 1955, as values recorded for the same two specimens are 0.846 and 0.840 ( 206 Pb/ 207 Pb). Overall, the findings point to a consistency between 1955 and 1964, when contamination events were reported in regional newspapers that mentioned a pollution event in October 1955 (unknown source) and an oil spill in May 1963 on the Saint-François River (Saint-Laurent et al 2008a;St-Laurent et al 2009). …”
Section: Discussionmentioning
confidence: 55%
“…The gap is also very small (±0.006) for 1955, as values recorded for the same two specimens are 0.846 and 0.840 ( 206 Pb/ 207 Pb). Overall, the findings point to a consistency between 1955 and 1964, when contamination events were reported in regional newspapers that mentioned a pollution event in October 1955 (unknown source) and an oil spill in May 1963 on the Saint-François River (Saint-Laurent et al 2008a;St-Laurent et al 2009). …”
Section: Discussionmentioning
confidence: 55%
“…Our previous work conducted on hydrocarbon-contamined layers found in alluvial soils (Saint-Laurent et al, 2008;2010a;2010b) showed marked differences in the Pb isotope values (e.g., 206 Pb/ 207 Pb, 208 Pb/ 206 Pb), suggesting separate spills of petroleum products in the rivers. For instance, the values obtained for Pb isotope ratios 206 Pb/ 207 Pb ranged from 0.124 to 0.175 ± 0.01 SD (Saint-Laurent et al, 2010b;2010c).…”
Section: Introductionmentioning
confidence: 90%
“…The mining sites at the Eustis-Capelton-Albert complex , located along the Massawippi River in south-central Québec, are an example of mining sites that have been abandoned, with untreated toxic waste having contaminated the water and aquatic organisms (Berryman et al, 2003). The former Eustis mine also served as a storage site for pulp and paper solid waste as well as for various discharges into the Massawippi River, including illegal discharges of oil which spread over more than 100 kilometers along the banks of the Massawippi and Saint-François rivers (Saint-Laurent et al, 2008;2010a). Traces of these spills, whether accidental or intentional, are easily visible in the soil of the riverbanks, especially in the Eustis, Capelton, Windsor, and Richmond sectors, forming dark-colored layers with varying thicknesses (2 to 90 cm) in soil profiles, and contain hydrocarbons, Pb, and other trace metal elements (Saint-Laurent et al, 2008;2010a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations